Recent Historiography of the Protestant Churches in America - Carter, Paul Allen (Church history, 1968)
Thirty-five years ago Lewis Vander Velde criticized his fellow historians for not having written more on the American churches. He charged that lay historians, “whose point of view is detached and objective,” had left the study of organized religion in the United States to “clergymen whose primary interest is religious” American historians recognized “the importance of the Church in colonial times,” but they had “too frequently assumed that its influence as a force in public affairs disappeared with the American Revolution”—even though the nation's recent experience with Prohibition ought to have taught them otherwise:Writers in an age when the Church is on the defensive fail to realize that the transformation which has put it in this position is much more a product of the last seventy years [i.e., 1862–1932] than of the previous seventy [i.e, presumably, 1792–1862]. In the time of our grandfathers, the Church was still a strong factor in the life of the nation; an institution led by intellectual giants, attended regularly by a large portion of the people, it exerted an important influence upon American life. … In 1860 politics and the Church still offered the greatest professional opportunities, and … in consequence the best minds were to be found there.